2011
DOI: 10.1161/circresaha.111.255737
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29 in Aortic Dilation: Implications for Aneurysm Formation

Abstract: Rationale: Aging represents a major risk factor for coronary artery disease and aortic aneurysm formation. MicroRNAs (miRs) have emerged as key regulators of biological processes, but their role in age-associated vascular pathologies is unknown.Objective: We aim to identify miRs in the vasculature that are regulated by age and play a role in age-induced vascular pathologies. Methods and Results:Expression profiling of aortic tissue of young versus old mice identified several ageassociated miRs. Among the signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
300
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(317 citation statements)
references
References 17 publications
(11 reference statements)
13
300
1
3
Order By: Relevance
“…In addition, reduced miR-126 and increased miR-125b expression results in increased endothelial inflammatory response protein secretion (36). miR-29 affects the production of collagen and elastin, and has important roles in maintaining arterial structural integrity (37). The results of the present study indicate that overexpression of miR-24 inhibits the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, reduced miR-126 and increased miR-125b expression results in increased endothelial inflammatory response protein secretion (36). miR-29 affects the production of collagen and elastin, and has important roles in maintaining arterial structural integrity (37). The results of the present study indicate that overexpression of miR-24 inhibits the proliferation and migration of endothelial cells.…”
Section: Discussionmentioning
confidence: 55%
“…[32][33][34][35] In fact, a significant regulation of the miR-29 family has been observed in old vs. young mice. 36 Very interestingly, the same miRs are mod- Several miRs are expressed in biologically relevant levels in most cells and tissues of the cardiovascular system. 5 In addition, miRs are seemingly released into the bloodstream, offering the opportunity to monitor the biological status of the cardiovascular system through the measurement of the expression pattern of specific miRs in the blood.…”
Section: Aging Calcification and Vessel Degenerationmentioning
confidence: 99%
“…33, 34 The association becomes much more interesting as it is known that the miR-29 family is expressed in high amounts in the aorta of aged mice, where it induces a decrease in elastin and collagen, with a general reduction of extracellular matrix, which is responsible for a higher susceptibility to aneurysm formation. 36 Interestingly, recent studies showed that the inhibition of the miR-29 family can be helpful in enhancing the structural stability of the vessel wall. In fact, the selective inhibition of miR-29 with a specific antagonist induced an increase in the expression of matrix proteins, which prevented aneurysm formation both in angiotensin II-induced aneurysm and in genetic models of aneurysm formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some recent studies clearly demonstrated the roles of miRNAs in the development of AAA [41][42][43][44]. Zampetaki et al [45] examined miR-195, a member of the miR-15 family.…”
Section: Resultsmentioning
confidence: 99%